Individuals with FOXP1 syndrome present with a complex neurobehavioral profile with high rates of ADHD, anxiety, repetitive behaviors, and sensory symptoms - M. Pilar Trelles; Tess Levy; Bonnie Lerman; Paige Siper; Reymundo Lozano; Danielle Halpern; Hannah Walker; Jessica Zweifach; Yitzchak Frank; Jennifer Foss-Feig; Alexander Kolevzon; Joseph Buxbaum (Molecular Autism, 2021)
Abstract Background FOXP1 syndrome is an autosomal dominant neurodevelopmental disorder characterized by intellectual disability, developmental delay, speech and language delays, and externalizing behaviors. We previously evaluated nine children and adolescents with FOXP1 syndrome to better characterize its phenotype. We identified specific areas of interest to be further explored, namely autism spectrum disorder (ASD) and internalizing and externalizing behaviors. Methods Here, we assess a prospective cohort of additional 17 individuals to expand our initial analyses and focus on these areas of interest. An interdisciplinary group of clinicians evaluated neurodevelopmental, behavioral, and medical features in participants. We report results from this cohort both alone, and in combination with the previous cohort, where possible. Results Previous observations of intellectual disability, motor delays, and language deficits were confirmed. In addition, 24% of the cohort met criteria for ASD. Seventy-five percent of individuals met DSM-5 criteria for attention-deficit/hyperactivity disorder and 38% for an anxiety disorder. Repetitive behaviors were almost universally present (95%) even without a diagnosis of ASD. Sensory symptoms, in particular sensory seeking, were common. Limitations As FOXP1 syndrome is a rare disorder, sample size is limited. Conclusions These findings have important implications for the treatment and care of individuals with FOXP1 syndrome. Notably, standardized testing for ASD showed high sensitivity, but low specificity, when compared to expert consensus diagnosis. Furthermore, many individuals in our cohort who received diagnoses of attention-deficit/hyperactivity disorder or anxiety disorder were not being treated for these symptoms; therefore, our findings suggest that there may be immediate areas for improvements in treatment for some individuals.